2021
DOI: 10.3390/nano11061540
|View full text |Cite
|
Sign up to set email alerts
|

Effective Poly (Cyclotriphosphazene-Co-4,4′-Sulfonyldiphenol)@rGO Sheets for Tetracycline Adsorption: Fabrication, Characterization, Adsorption Kinetics and Thermodynamics

Abstract: The development of excellent drug adsorbents and clarifying the interaction mechanisms between adsorbents and adsorbates are greatly desired for a clean environment. Herein, we report that a reduced graphene oxide modified sheeted polyphosphazene (rGO/poly (cyclotriphosphazene-co-4,4′-sulfonyldiphenol)) defined as PZS on rGO was used to remove the tetracycline (TC) drug from an aqueous solution. Compared to PZS microspheres, the adsorption capacity of sheeted PZS@rGO exhibited a high adsorption capacity of 496… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(69 reference statements)
1
5
0
Order By: Relevance
“… Proposed mechanism of tetracycline decontamination through PZS@rGO involving π–π stacking, electrostatic interactions, H-bonding, and Lewis acid–base interactions. 118 Reprinted with permission from ref ( 118 ). …”
Section: Applications Of the Cyclomatrix Type Of Polyphosphazenesmentioning
confidence: 99%
See 2 more Smart Citations
“… Proposed mechanism of tetracycline decontamination through PZS@rGO involving π–π stacking, electrostatic interactions, H-bonding, and Lewis acid–base interactions. 118 Reprinted with permission from ref ( 118 ). …”
Section: Applications Of the Cyclomatrix Type Of Polyphosphazenesmentioning
confidence: 99%
“…Their porous morphology, large surface area hollow in structure, abundant hydroxyl groups, presence of heteroatoms, active −NH 2 groups, and π–π stacking make polyphosphazenes excellent candidates as adsorbents (shown in Figure ). ,, …”
Section: Applications Of the Cyclomatrix Type Of Polyphosphazenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphosphazenes are the novel genre of polymers with organic–inorganic nature and an inorganic (−P=N−) bone structure with a multiplicity of side functional groups, for example, organometallic, inorganic, or organic groups. 18 These features of polyphosphazene hybrid materials make them promising candidates for the biomedical carriers and immobilizing the metal ions, which leads to the good dispersion of bimetallic NPs. Yan et al reported the Ag–Au NPs impregnated over the PZS [poly(cyclotriphosphazene- co -4,4′-sulfonyldiphenol)] nanotube with rich −OH groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, achieving a facile method for the fabrication of one-dimensional polymer nanotubes through self-controlled dimensions under environment-friendly conditions is a task for the researcher. Polyphosphazenes are the novel genre of polymers with organic–inorganic nature and an inorganic (−PN−) bone structure with a multiplicity of side functional groups, for example, organometallic, inorganic, or organic groups . These features of polyphosphazene hybrid materials make them promising candidates for the biomedical carriers and immobilizing the metal ions, which leads to the good dispersion of bimetallic NPs.…”
Section: Introductionmentioning
confidence: 99%